STUDI HUKUM ISLAM TENTANG PERAN BABYSITTER DALAM MENGGANTIKAN KEWAJIBAN HADHANAH TERHADAP ANAKNYA DI “TPA MEDIA CINTA ILMU” KELURAHAN TLOGOANYAR KECAMATAN LAMONGAN KABUPATEN LAMONGAN - Inti Haul Khusna; Nur Hasan; Dwi Ari Kurniawati (Jurnal Hikmatina, 2019)
Islam teaches the obligatory care of parents for their children for the continuity of their children's future, but lately there have been few parents who carry out their obligations due to economic factors, so they leave their children in TPA under the supervision of a babysitter who replaces their parents' duties. The purpose of this study is to describe the way babysitters take care of children in "TPA Media Cinta Ilmu" both in theory and practice and are in accordance with Islamic Law and can replace the obligations of parents in hadhanah to their children or not. The data collection method used is the method of observation, interviews and documentation and using a type of qualitative research. The results of the study are about the way the babysitter is educating, guiding, nurturing, caring for and giving affection as their child like learning religion (the practice of prayer, tahfidz quran and reading iqro '), how the babysitter can replace the hadhanah's obligations to the child by entrusting their children in the landfill in order to get care, appropriate education in Islam, every person who educates them, whether parents or other educators will also get the reward as the child gets reward for the good deeds he does. Key word: Islamic law, babysitter, hadhanah